2020
DOI: 10.1159/000506095
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Examination for Fetuses with Increased Fetal Nuchal Translucency by Genomic Technology

Abstract: This study aims to investigate the value of chromosomal microarray analysis (CMA) and whole exome sequencing (WES) in fetuses with increased nuchal translucency (defined as NT above the 95th centile for the crown-rump length). A total of 374 singleton pregnancies with gestational ages ranging from 11 to 13 + 6 weeks were investigated. Ultrasound displayed increased NT and no detectable structural malformations in these fetuses. Pregnancies were divided into 4 groups according to the NT values: 95th centile-3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…During the iterative review, 90 series of structurally abnormal fetuses that included fetuses with increased NT were identified (Figure 1). Among the 101 abstracts identified, 17 full-text articles were reviewed and 10 were deemed eligible and included in the study [17][18][19][20][21][22][23][24][25][26] . In addition, our own series, which was presented previously as an abstract at an international conference, was included 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the iterative review, 90 series of structurally abnormal fetuses that included fetuses with increased NT were identified (Figure 1). Among the 101 abstracts identified, 17 full-text articles were reviewed and 10 were deemed eligible and included in the study [17][18][19][20][21][22][23][24][25][26] . In addition, our own series, which was presented previously as an abstract at an international conference, was included 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 11 studies, three included only cases of increased NT (of which two included isolated increased NT only 23,24 and one included both isolated cases and cases with an associated abnormality 22 ), one study included a fetus with signs of hydrops 25 , while the remaining seven studies included fetuses with various structural anomalies (Table 1). Only cases with isolated increased NT at the time of genetic testing were selected for this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The first studies on prenatal WES suggested a 10-25% increase in diagnostic yield in fetuses with various sonographic abnormalities (42)(43)(44). Approximately six studies on prenatal WES have included fetuses with an isolated increased NT and normal microarray results (16,42,(45)(46)(47)(48). The diagnostic yield of prenatal WES in these studies varies from 0 to 13% with an average of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported data on the use of prenatal microarray in fetuses with (isolated) increased NT, with the first report starting as early as 2003 (13) and approximately five English studies in the years 2020 and 2021 (14)(15)(16)(17)(18). These studies show a relatively wide range (0-20%) of additional genetic findings in fetuses with increased NT with regard to prenatal microarray when compared to standard karyotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, larger cohorts of fetuses with isolated and non‐isolated increased NT have been studied with sequencing after normal microarray (Table 5). 42–48 Yang et al. performed trio exome sequencing on 73 fetuses with isolated first trimester increased NT ≥3.5 mm and normal CMA 45 .…”
Section: Genomic Testingmentioning
confidence: 99%